Development of low-pressure electric steam heater - Mekhtiyev, Ali; Breido, Iossif; Buzyakov, Rustam; Neshina, Yelena; Alkina, Aliya (Eastern-European Journal of Enterprise Technologies, 2021)
The study was devoted to solving the issue of creating new electric heating devices that can be used in autonomous heat supply systems. The issues were resolved by developing an original low-pressure electric steam heater. The study was aimed at improving the efficiency of heat supply systems for buildings and structures. Given the current trends in the global striving for energy conservation, it cannot be fully realized without the introduction of high-tech and low-energy-consuming electrical equipment. As a result of theoretical studies of a heat pipe with an electric heater, a design of an electrovacuum heating element has been developed. The low-pressure electric steam heater can be used in heat supply systems of autonomous users. Thermal energy transfer is currently accompanied by substantial energy losses since the heat carrier has to pass considerable distances. Switching of the facility to the heating plant is impossible in some cases because of technical problems or significant material costs for laying pipelines. As a result of the study, the dependence of heating the heat pipe at various volumes of the heat carrier and mass of the pipe itself was established. When a certain mass is reached, the temperature of the heating surfaces can reach 70 °C which is considered acceptable. The experimental data obtained have made it possible to develop an electric heater of new generation with a fundamentally new design of the heating element. It combines the efficiency of an electric spiral and comfortable warmth from a traditional radiator. This heater is an explosion and fire-safe and can be integrated into the Smart Home system